Identification of a MicroRNA‐E3 Ubiquitin Ligase Regulatory Network for Hepatocyte Death in Alcohol‐Associated Hepatitis. Issue 5 (16th March 2021) - Fan, Xiude; Wu, Jianguo; Poulsen, Kyle L.; Kim, Adam; Wu, Xiaoqin; Huang, Emily; Miyata, Tatsunori; Sanz‐Garcia, Carlos; Nagy, Laura E.
Abstract : We aimed to identify a microRNA (miRNA)‐E3 ubiquitin ligase regulatory network for protein substrates enriched in cell death pathways and investigate the underlying molecular mechanisms in alcohol‐associated hepatitis (AH). An miRNA‐E3 ubiquitin ligase regulatory network for protein substrates enriched in cell death pathways was constructed using integrated bioinformatics analysis. Differentially expressed hub miRNAs (GSE59492 ) and their validated miRNA target genes (GSE28619 ) were identified in the liver of patients with AH compared with healthy controls. Liver samples from patients with AH and healthy individuals and mice exposed to Gao‐binge (acute on chronic) ethanol were used for experimental validation. Using hub miRNAs identified by weighted correlation network analysis, a miRNA‐E3 ubiquitin ligase regulatory network was established based on 17 miRNAs and 7 E3 ligase genes targeted by these miRNAs that were down‐regulated in AH. Among the miRNAs in this regulatory network, miR‐150‐5p was the only miRNA regulating the E3 ligase cytokine‐inducible SH2 containing protein (CISH), the E3 ligase that regulates the largest number of substrates among all E3 ligase family members. Therefore, the CISH regulatory pathway for ubiquitinated substrates was selected for subsequent experimental validation. Consistent with the bioinformatics analysis results, expression of miR‐150‐5p was markedly increased, while CISH was decreased, in the livers of patients with AH and mice exposed to Gao‐binge ethanol. Moreover, ubiquitination of Fas‐associated protein with death domain, a predicted CISH substrate involved in the regulation of programmed cell death, was reduced in livers from mice after Gao‐binge ethanol. Conclusion: Identification of the miRNA‐E3 ubiquitin ligase regulatory network for protein substrates enriched in the cell death pathways provides insights into the molecular mechanisms contributing to hepatocyte death in AH. Abstract : This study identifies a microRNA‐E3 ubiquitin ligase regulatory network for protein substrates enriched in cell death pathways. We report that expression of miR‐150‐5p was elevated in AH and experimentally verified the changes in the key components in this miR‐150‐5p‐CISH‐FADD regulatory network in the liver from both patients with AH and a murine model of acute‐on‐chronic ethanol exposure.image